2019
DOI: 10.1109/access.2019.2929230
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic PET Image Denoising Using Deep Convolutional Neural Networks Without Prior Training Datasets

Abstract: Deep learning has attracted growing interest for application to medical imaging, such as positron emission tomography (PET), due to its excellent performance. Convolutional neural networks (CNNs), a facet of deep learning requires large training-image datasets. This presents a challenge in a clinical setting because it is difficult to prepare large, high-quality patient-related datasets. Recently, the deep image prior (DIP) approach has been devised, based on the fact that CNN structures have the intrinsic abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 39 publications
1
78
0
Order By: Relevance
“…Consistent with previous studies [25,26,33], the findings presented here suggest that image quality, in terms of interpixel spatial variance and measurement reproducibility, were significantly improved. However, we found that these findings might not always translate directly into clinical improvements-the uptake in small foci was sometimes not accurately quantified, and lesion detection and localization realized less benefit.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies [25,26,33], the findings presented here suggest that image quality, in terms of interpixel spatial variance and measurement reproducibility, were significantly improved. However, we found that these findings might not always translate directly into clinical improvements-the uptake in small foci was sometimes not accurately quantified, and lesion detection and localization realized less benefit.…”
Section: Discussionsupporting
confidence: 92%
“…Nowadays deep learning is the most active research area, and much work has been reported in PET denoising [13][14][15][16][17][18][19]. Deep learning denoising is effective and has better results than traditional methods.…”
Section: Discussionmentioning
confidence: 99%
“…In DIP, no pre-training dataset is needed, a convolutional neural network (CNN) is initialized with random parameters, and only random noise is prepared as the network input. Research related to DIP has focused on natural image denoising, inpainting, super-resolution reconstruction [33,34], PET image reconstruction [35,36], and even compressed sensing recovery problems [37].…”
Section: Introductionmentioning
confidence: 99%